Research of court evidence of the time of Kievan Rus accomplished by professor O. I. Paliumbetskyi (1811-1897) - V. A. Grechenko (Law and Safety)
The objective of the article is to highlight the scientific work of Professor O. I. Paliumbetskyi in the field of the history of Old Russian law. This objective is specified in the following tasks: to show how the witnesses testimonies were evaluated by scholars; what significance he gave to probations in the system of court evidence of the time of Kievan Rus; where he saw the peculiarities of the Russian legislation regarding court evidence in comparison with the German one.